Over bekken etter vann? Fra lokalt økomuseum til globalt mangfoldsmuseum - Vangen, Lisa; Jakobsen, Lise (Tidsskrift for kulturforskning, 2024)
In recent decades, museums have been taken into a discourse where professionalism, relevance, democracy, participation, and diversity are the benchmarks for quality. Through professionalization, knowledge of local identity and culture is put into academic and scientific frames. Increased globalization affects our understanding of culture and identity, and museums must reflect society’s cultural diversity. This is expressed through political intentions and guidelines, but it is up to the museums to design their role in society. For Nord-Troms Museum, this has meant a transition from being an ecomuseum to becoming a museum of diversity. This article shows that there is no clear break between the ecomuseum and the diversity museum. The presentation of the museum facilities and the population’s expectations of the museum are in many ways the same as 30 years ago. Communication must be adapted to the changing conditions. One way is by telling multiple stories that highlight the diversity of the region’s past and connect it more closely to people in society today.